2017
DOI: 10.2147/cia.s136906
|View full text |Cite|
|
Sign up to set email alerts
|

Frequency of frailty and its association with cognitive status and survival in older Chileans

Abstract: BackgroundAge-associated brain physiologic decline and reduced mobility are key elements of increased age-associated vulnerability.ObjectiveTo study the frequency of frailty phenotype and its association with mental health and survival in older Chileans.MethodsFollow-up of ALEXANDROS cohorts designed to study disability associated with obesity in community-dwelling people 60 years and older living in Santiago, Chile. At baseline, 2,098 (67% women) of 2,372 participants were identified as having the frailty phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
10

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 34 publications
4
26
0
10
Order By: Relevance
“…The regression analysis adjusted by gender, age and education level showed that older adults with frailty had a 100% increased chance of presenting MCI 33 . In a study involving Chilean older adults, individuals with frailty had 3.93 times more chance of presenting MCI 34 . A study conducted in Brazil, with 51 prefrail and frail older adults used a similar MMSE cut-off.…”
Section: Discussionmentioning
confidence: 97%
“…The regression analysis adjusted by gender, age and education level showed that older adults with frailty had a 100% increased chance of presenting MCI 33 . In a study involving Chilean older adults, individuals with frailty had 3.93 times more chance of presenting MCI 34 . A study conducted in Brazil, with 51 prefrail and frail older adults used a similar MMSE cut-off.…”
Section: Discussionmentioning
confidence: 97%
“…A su vez, el SF se asoció con deterioro cognitivo y depresión, de manera similar a publicaciones previas que han llegado a sugerir que aunque no se considera como un criterio del SF, la salud mental forma parte del fenotipo de fragilidad [31] . Sargent L, et al [32] en una reciente revisión sistemática, proponen que el SF y el deterioro cognitivo tendrían mecanismos fisiopatológicos comunes.…”
Section: Discussionunclassified
“…Para isto, o cuidado primário parece ser o melhor ambiente para realizar esta tarefa no cuidado dos idosos (Espinoza, Walston, 2005;Gray et al, 2016) (Cesari et al, 2016b;Gilardi et al, 2018). Os critérios de Fried para SF parecem ser, até o momento, os que melhor se encaixam nestes pressupostos (Woo et al, 2012;Op het Veld et al, 2015;Le Cossec et al, 2016;Albala et al, 2017;Ensrud et al, 2018).…”
Section: Diagnóstico Prognóstico E Manejo Da Síndrome De Fragilidadeunclassified
“…Como apresentado na introdução, esta relação pode estar relacionada à múltiplos fatores subjetivos importantes na avaliação de pacientes idosos em geral, como fatores sociais e estados depressivos (Albala et al, 2017;Park et al, 2018;Tsutsumimoto et al, 2018), uso de múltiplas medicações (polifarmácia) (Gutiérrez-Valencia et al, 2018), número e tipos de comorbidades (Onder et al, 2018), suporte familiar, desnutrição (Chye et al, 2018), condições de moradia, violência doméstica, aspectos culturais específicos e condições financeiras (Grden, CRB, 2015;Cho et al, 2017 (Siriwardhana et al, 2018;Veninsek, Gabrovec, 2018;Windhaber et al, 2018). Na tentativa de melhor elucidar as relações entre a SF e DP, encontramos associação entre o tempo de caminhada no momento inicial do estudo e a evolução para SF (FRAGILIDADE FINAL) e pior avaliação na escala UPDRS após 6 meses (UPDRS FINAL).…”
Section: Procedimentos Do Projetounclassified
See 1 more Smart Citation